A GIS-Based Approach for the Sustainable Management of Livestock Effluents on Alpine Meadows - Gubert, Francesco; Silvestri, Silvia; Pecile, Angelo; Grandi, Luca (Frontiers in Sustainable Food Systems, 2018)
Sustainable livestock effluent management is becoming an increasingly important issue in mountain areas, with particular regard to the agro-environmental performance of forage production and the social acceptability of organic fertilizer application in mixed urban-rural contexts. The present paper proposes a GIS-based methodological approach to the management and planning of digestate spreading on hay meadows, based on the integration of geo-morphological, agro-botanical and spatio-functional data about cultivated agricultural land. The proposed methodology was tested in a case-study Community of the Italian Alps, with 7 dairy farms operating an anaerobic digestion plant. Nitrogen production by cattle was quantified and compared to sustainable nitrogen requirements of cut meadows, computed at the single-plot level through agro-botanical typisation of swards. Subsequently, spreading restrictions provided by national and local regulations were spatially implemented. Farm-tailored nitrogen balances and digestate spreading plans were designed to help livestock farms adjust effluent spreading patterns according to meadow type and surface runoff risk. Findings are transferrable to other mountain regions based on cattle farming and grassland management.